Unsuccessful Treatments of "Writer's Block": A Meta-Analysis. Issue 1 (August 2014) - McLean, Derrick C.; Thomas, Benjamin R.
A wide literature of the unsuccessful treatment of writer's block has emerged since the early 1970's. Findings within this literature seem to confer generalizability of this procedure; however, small sample sizes may limit this interpretation. This meta-analysis independently analyzed effect sizes for "self-treatments" and "group-treatments" using number of words in the body of the publication as indication of a failure to treat writer's block. Results of the reported findings suggest that group-treatments tend to be slightly more unsuccessful than self-treatments.